Law Enforcement Against Companies Accused of Illicitly Providing Facilities for Jarimah in Banda Aceh City's Jurisdiction - Putri Amalina; Mohd. Din; Ali Abubakar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The special autonomy granted to Aceh Province allows for the implementation of Islamic criminal law (jinayat), yet challenges remain in law enforcement, particularly against corporations that provide facilities for Jarimah. Despite the enactment of Qanun Number 6 of 2014 on Hukum Jinayat, prosecutions have largely focused on individuals, while companies such as hotels, boarding houses, and cafés frequently escape accountability, even when their facilities are used to commit acts such as khalwat, maisir, and zina. This study aims to examine the enforcement mechanisms targeting such corporate entities within the jurisdiction of Banda Aceh City. Employing empirical legal research methods, the study utilizes qualitative analysis based on field observations, interviews with stakeholders, and a review of legal documents. The findings indicate that law enforcement efforts are hampered by five major factors: vague and incomplete legal provisions; limited knowledge and training among investigators; inadequate human resources and supporting infrastructure; a lack of public support; and deeply rooted cultural practices that often favor informal resolutions over formal prosecution. Despite the legal possibility of corporate liability under the qanun, enforcement remains weak due to unclear definitions, particularly concerning intent and the element of facilitation. The study concludes that the effectiveness of law enforcement in this domain is critically undermined by structural and normative deficiencies. Therefore, reform is urgently needed, including amendments to legal texts, comprehensive investigator training, and public engagement strategies to ensure corporate accountability in supporting the implementation of syari’at Islam in Aceh.